Life-satisfaction of middle class families in a metropolitan city - Saha , Krishna; Chel, Swati Roy (Gyan Management Journal, 2010)
the years, the relationship between life satisfaction and job satisfaction has been extensively But the results have not proved conclusive in demonstrating the causal nature of the onship. The present study investigates the inter-correlation between job satisfaction, life : :-,_.·action, life satisfaction over time and health for male and female employees belonging to middle : , families in a metropolitan city (Kolkata). Life satisfaction over time and health were included in :·, _,resent study because these two aspects of life influence both job and life satisfaction of an·:idual employee. The relationships of the socio-demographic variables with life and job : :- ,faction were also examined. The data was obtained from a questionnaire-based survey from a : "’"’.p/e ofl 74ma/eand 83 female employees working in differentspheres of life.The data was collected from 120 housewives. Factor analysis was conducted . -:;·estigate how housewives of middle class families spend their time.·: present study also investigates the life-satisfaction of housewives and how they feel about their